2016
DOI: 10.12681/ppej.207
|View full text |Cite
|
Sign up to set email alerts
|

Narrative skills in preschool and first grade children

Abstract: The aim of the study was to investigate the developmental path of narrative skills of preschool and primary school children. Two hundred thirty seven Greek-speaking children from various regions of Greece participated in the study. They were separated in three age groups: 4-5, 5-6 and 6-7 years old. Retelling and narrative production skills were evaluated. Correlations between the two narrative skills were investigated. Four illustrated stories were used (two stories for retelling and two stories for narrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The results indicated that older children outperformed younger ones on all macrostructure measures. Similar developmental findings were reported by Kanellou, Korvesi, Ralli and Mouzaki (2016) in their study with 4-7 years old Greek children. Last, according to Wehmeier (2021), the narrative comprehension results pointed to significant age effect among three age groups (4;6-4;11, 5;0-5;5, 5;6-5;11) in children's retellings of stories.…”
Section: Narrative Developmentsupporting
confidence: 90%
“…The results indicated that older children outperformed younger ones on all macrostructure measures. Similar developmental findings were reported by Kanellou, Korvesi, Ralli and Mouzaki (2016) in their study with 4-7 years old Greek children. Last, according to Wehmeier (2021), the narrative comprehension results pointed to significant age effect among three age groups (4;6-4;11, 5;0-5;5, 5;6-5;11) in children's retellings of stories.…”
Section: Narrative Developmentsupporting
confidence: 90%
“…It was designed to cover a wide range of language skills (semantic knowledge, phonological awareness and processing, morphological awareness, oral discourse and pragmatics) in children aged 4-7 years. Test items within each task assessing the various language domains were arranged in ascending order of difficulty adhering to floor and ceiling rules that were determined during extensive pilot testing (Kanellou, Korvesi, Ralli, Mouzaki, Antoniou, Diamanti & Papaioannou, 2016;Ralli, Kazali, Kanellou, Mouzaki, Antoniou, Diamanti & Papaioannou, submitted). Task presentation and item order within each task were the same for all participants who were initially trained through two practice items that were followed by proper feedback and repeated up to three times if needed.…”
Section: Language Measuresmentioning
confidence: 99%